It is not all about sodium: revealing tissue specificity and signalling roles of potassium in plant responses to salt stress - Wu, Honghong; Zhang, Xianchen; Giraldo, Juan Pablo; Shabala, Sergey (Plant and soil, 2018)
Background Salinity is a global issue threatening agricultural production systems across the globe. While the major focus of plant salinity stress tolerance research has been on sodium, the transport and physiological roles of K+ in plant salt stress response has received less attention. This review attempts to bridge this knowledge gap. Scope The major emphasis is on newly proposed K+ signalling roles and plant salt tolerance cell- and tissuespecificity. In addition to summarizing the importance of K+ retention for plant salt tolerance, we focus onaspects that were not the subject of previous reviews including (1) the importance of HAK/KUP family of transporters in K+ uptake in salt stressed plants and its possible linkage with Ca2+ and ROS signalling; (2) control of xylem K+ loading in salt stressed plants, control of phloem K+ recirculation in salt stressed plants and the potential importance of plant's ability to efficiently coordinate K+ signals between root and shoot; (3) the buffering capacity of the vacuolar K+ pool; and (4) mechanisms of restoring the basal cytosolic K+ levels by coordinated activity of tonoplast K+-permeable channels. Conclusions Overall, this review emphasises the need to fully understand the newly emerging roles of K+ and regulation of its transport for improving salinity stress tolerance in plants.